PENINGKATAN KUALITAS PEMBELAJARAN DARING MATA KULIAH BAHASA DAERAH MELALUI PERANCANGAN DESAIN PEMBELAJARAN - I Wayan Agus Gunada (Padma Sari: Jurnal Ilmu Pendidikan, 2022)
The purpose of writing this article is to describe preparing learning design in local language courses. One of the success factors of learning, both face-to-face and online, is seen from the final results, both assessment and measurement of learners' learning outcomes, and dependent on how an educator can design a series of teaching and learning activities. So that the planning, implementation and evaluation of the learning process is a complete unity process. Likewise, in Local Language courses, it is necessary to design a series of learning activities that support the online learning process so that learning achievements a expected to be mastered by learners. This qualitative research is carried out with participant observation models during the design process and implementation of learning design until the end of learning, literature studies related to similar studies and online interviews with learners. Based on the research results obtained, to determine the learning design model to be implemented, it is necessary to understand the characteristics of local language courses based on curriculum demands. There are common obstacles encountered in designing and implementing learning in the disruption of internet access and student ability related to the lack of quotas. The evaluation results show that the designed learning design needs to be refined and reviewed on the strategies and online learning media used related to the obstacles faced by learners. It has hoped that through the development of this learning design, it can become a reference library and valuable for educators in designing a learning process, especially in online learning activities during the Covid-19 pandemic